Integral sets of systems of difference equations - Gulov, Kh. M.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The problem of existence of integral sets of systems of difference equations is studied. We establish sufficient conditions for the existence of these sets and their stability. For the system under consideration, the behavior of trajectories that originate in a sufficiently small neighborhood of integral sets is investigated.